PEMBELAJARAN KOOPERATIF TEAM GAMES TOURNAMENT DAN LEARNING CYCLE PADA MATA PELAJARAN ELEKTRONIKA - Depari, Ganti (INVOTEC, 2011)
This study discusses the comparison of the effectiveness of Team games tournament cooperative learning model and learning cycle model on students’ achievement. Both of these methods emphasize a situation where students work in small groups and help each other to learn the course material. Students become the center of the learning activity (student-centered). This study uses quasi-experiment method, with subjects consisting of two classes, i.e. class X TAV 3 and X TAV 4. The results show that there is a difference in average academic achievement between learning cycle model (0,58) and team games tournament (0,73). tobt = 3,69, thus tobt = 3,69 ttable(0.95)(58) = 1,676. It is concluded that a learning activity with TGT cooperative learning model is better than a learning activity with learning cycle model in improving students’ achievement.